Listeria monocytogenes multifocal cerebritis in an immunocompetent adult - Milošević, Branko; Urošević, Aleksandar; Nikolić, Nataša; Milošević, Ivana; Poluga, Jasmina; Tošić, Tanja; Jovanović, Milica (Vojnosanitetski pregled, 2021)
Introduction. Multifocal cerebritis is a rare and severe disease and just a several cases caused by Listeria monocytogenes were described in the literature. Case report. A 64 year old man was admitted to the hospital with disturbed consciounsness (Glasgow Coma Scale score: 9) after being febrile for 16 days with history of fever, headache and middle ear pain. He did not have any other comorbidities neither he was immunocompromised. Penicillin allergy was noted for him. On neurologic exam, meningeal or focal neurologic signs were not evident, but computed tomography (CT) brain scan with contrast injection showed 3 hypodense zones in the occipital and 1 in the right temporal lobe. Laboratory findings in blood and cerebrospinal fluid (CSF) were indicative for the infectious nature of changes in the endocranium (multifocal cerebritis). Initial therapy was the combination of cefotaxime, amikacin and metronidazole, but after the isolation of L. monocytogenes from CSF and blood culture, therapy was switched to co-trimoxazole. Recovery of consciouscness with establisment of alert state occurred after 6 days of co-trimoxazole administration. Total therapy took 36 days. During that period all clinical and laboratory parameters normalized. The patient was discharged as recovered, with sequelas of amnesia and slurring of speech. Conclusion. In the treatment of multifocal cerebritis caused by L. monocytogenes, adequate choice and long-term therapy with antibiotics are necessary. The drug of choice is ampicillin but in the case of allergy to it, co-trimoxazole is a good replacement.
Keywords: meningitis, listeria; listeriosis; anti-infective agents; drug combinations; tomography; trimetoprim, sulfamethoxazole drug combination